Application of highly deviated well injection technology in Huabei Oilfield. (September 2020) - Wang, Yao; Han, Mingzhe; Chen, Junzheng; Li, Ran; Zhang, Xu; Liu, Zhijuan; Wang, Shuangyan; Wei, Yuhao; Cheng, Xiangfa; Xiong, Wei; Liu, Dayong; Huang, Bohua; et al.
Abstract: With the deepening of oilfield development, the amount of highly deviated (≥30°) layered water injection wells have increased year by year. In order to solve the technical bottlenecks such as poor sealing of the columns and short effective period of dispensing. The self-supporting step-by-step releasable packers with the outer diameter of 114mm and the highly deviated well ball seat are developed. The packer integrates the function of centering-righting, ball centering, spiral righting and stepping unblocking and the ball seat has self-locking function and able to meet the requirements of pipe string used in highly deviated wells within 60°. Through the field application, a highly deviated well-dispensing process technology suitable for the characteristics of Huabei Oilfield has been formed, it has a strong popularization and application value.